2020
DOI: 10.3201/eid2606.190975
|View full text |Cite
|
Sign up to set email alerts
|

Melioidosis in a Resident of Texas with No Recent Travel History, United States

Abstract: B urkholderia pseudomallei, which causes melioidosis, is a gram-negative saprophytic bacterium endemic to tropical and subtropical environments worldwide; to our knowledge, isolation from the continental United States has not been reported (1-3). The most overrepresented risk factor for melioidosis is diabetes mellitus (3,4). B. pseudomallei is resistant to many antimicrobial drugs (3). Laboratory exposures might occur without appropriate biosafety precautions (2,5). Surveillance is challenging because melioid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 14 publications
(10 reference statements)
2
29
1
Order By: Relevance
“…This is similar to recent studies from Laos and Myanmar [ 25 , 26 ], which suggest a dynamic process of more recent possibly anthropogenically driven regional dispersal of Bp, in addition to the ancient intercontinental dispersals originally from Australia, where Bp is thought to have arisen [ 12 ]. The spread of Bp in the Americas is considered a more recent phenomenon, with recent evidence suggesting that Bp may now be endemic in the United States [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to recent studies from Laos and Myanmar [ 25 , 26 ], which suggest a dynamic process of more recent possibly anthropogenically driven regional dispersal of Bp, in addition to the ancient intercontinental dispersals originally from Australia, where Bp is thought to have arisen [ 12 ]. The spread of Bp in the Americas is considered a more recent phenomenon, with recent evidence suggesting that Bp may now be endemic in the United States [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Melioidosis is an important cause of infectious disease mortality in the Western Pacific region and in Southeast Asia (SEA) [ 1 , 2 ]. Although historically known to be endemic to SEA and northern Australia, cases are now increasingly being reported worldwide [ 3 , 4 ]. Melioidosis is caused by the environmental saprophyte Burkholderia pseudomallei ( Bp ), a gram-negative bacillus that is intrinsically resistant to a broad range of antibiotics, including aminoglycosides [ 5 ].…”
mentioning
confidence: 99%
“…Prior studies have shown that B. pseudomallei originally evolved in the environment of Australia and subsequently spread to Southeast Asia and East Asia during the last glacial period (between 16 and 225 thousand years ago) 12 . From Asia, B. pseudomallei subsequently spread to Madagascar and Africa and more recently from West Africa to the Americas (between 1650 and 1850), likely linked to the slave trade 12 15 . This strong geographic signal of the B. pseudomallei genome is notably due to infection in humans and animals being acquired directly from an environmental source, with human–human and zoonotic transmission being exceedingly rare.…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing surveillance and diagnostic capabilities have revealed that Bpm is also found in the soil in the Middle East, sub-Saharan Africa, the Caribbean islands, and the Americas [ 1 ]. Recently, a non-travel related case of melioidosis was identified in Texas and, together with another prior case in the same area, suggest that Bpm might be present in the soil of the continental United States [ 2 ]. It has been estimated that there are 165,000 cases of melioidosis a year with 89,000 deaths globally [ 1 ].…”
Section: Introductionmentioning
confidence: 99%